Perbandingan Analisis Pergerakan Agregat dan Distribusi Void Akibat Pengaruh Pemadatan antara Campuran RAP dan Agregat Baru Bergradasi Cooper - Wicaksono, Andang; , Ir. Sri Sunarjono, M.T, PhD (2017)
Reclaimed Asphalt Pavement (RAP) is the dismantling of damaged old road pavement. The quality of RAP mixtures properties is not competitive yet compared to aggregate fresh material because of the declining quality of asphalt mixture containing RAP material, however, the use of RAP material as basic material of road pavement recycle is still possible. The selection of gradation and characteristics of mixture during compaction strongly affects bridle power of aggregate movement and the total value of air cavity in each layer of the mixture, so that maximum density value can be achieved. Based on the problems, it is necessary to perform observation on aggregate movement in order to know the mixture characteristics during compaction and void distribution in order to determine the amount of air voids in each layer of the mixture. This research was conducted by a laboratory test using RAP materials compared to fresh aggregate. This research analyzed the aggregates movement during compaction by observing the movement of rock synthesis with total collisions of 2x25, 2x50, and 2x75, so movement patterns will be known. Meanwhile, for the void distribution analysis, it was performed by cutting the specimen into 3 parts and then analyzed the value of air cavity of each layer. Based on observations result of the movement of rock synthesis of horizontal and vertical pieces, it was shown that aggregate fresh mixture had more dynamic movement than the RAP, while testing for void distribution indicated that the total air cavity of aggregate fresh material was more uniform/homogeneous compared to RAP in each layer of the test specimen. This happens because there was indication that the old bitumen contained in the RAP became one of aggregate movement inhibitors. As a result, it was difficult to compact mixture of RAP material; therefore, density of asphalt mixture containing RAP material was still low compared to fresh aggregate. This can be proven by analyzing mixture characteristics during compaction and by observing aggregates movement, as well as testing the void distribution of asphalt mixture containing RAP material and fresh aggregate.